2020
DOI: 10.3390/cancers12102792
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Methylation at H3K27: A Trick or Treat for Cancer Cell Plasticity

Abstract: Properly timed addition and removal of histone 3 lysine 27 tri-methylation (H3K27me3) is critical for enabling proper differentiation throughout all stages of development and, likewise, can guide carcinoma cells into altered differentiation states which correspond to poor prognoses and treatment evasion. In early embryonic stages, H3K27me3 is invoked to silence genes and restrict cell fate. Not surprisingly, mutation or altered functionality in the enzymes that regulate this pathway results in aberrant methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 357 publications
(402 reference statements)
1
21
0
Order By: Relevance
“…Although f-Het covers a substantial part of the genome, it remains relatively understudied in its response to DSBs. Since f-Het is important in many biological processes, such as X-chromosome inactivation in female mammals, genomic imprinting, stem cell maintenance, and cell differentiation, it is not surprising that polycomb misregulation can lead to diseases such as cancer [ 123 ]. It is, therefore, essential to understand how this silenced state is maintained during the repair of DSBs.…”
Section: Facultative Heterochromatinmentioning
confidence: 99%
“…Although f-Het covers a substantial part of the genome, it remains relatively understudied in its response to DSBs. Since f-Het is important in many biological processes, such as X-chromosome inactivation in female mammals, genomic imprinting, stem cell maintenance, and cell differentiation, it is not surprising that polycomb misregulation can lead to diseases such as cancer [ 123 ]. It is, therefore, essential to understand how this silenced state is maintained during the repair of DSBs.…”
Section: Facultative Heterochromatinmentioning
confidence: 99%
“…KDM6B, a member of Jumonji domain‐containing proteins, acts as a histone demethylase and is an important regulator in multiple cellular processes, such as cell development, differentiation, senescence and inflammation. More importantly, a large body of data has shown the association of KDM6B abnormality with tumor progression [ 2 ]. Our previous study also showed that KDM6B inhibited the stem cell‐like properties of breast cancer by inhibiting the expression of OCT4.…”
Section: Discussionmentioning
confidence: 99%
“…Lysine‐specific demethylase 6B (KDM6B), also known as Jumonji domain‐containing protein 3, is a member of the histone demethylases. It specifically catalyzes the removal of the trimethyl group from H3K27 lysine residue to active chromatin conformation [ 2 , 3 ]. It has been shown that KDM6B plays essential roles in development, differentiation, cell senescence and inflammation [ 4 , 5 , 6 ].…”
mentioning
confidence: 99%
“…These data confirmed that the modulation (increase or decrease) of expression of each enzyme promoted EMT. Das and Taube [26] indeed highlighted the difficulty of addressing the precise contribution of these enzymes in a recent review.…”
Section: Discussionmentioning
confidence: 99%